Environmental Sustainability for Infection Prevention and Control (IPC) in Healthcare Facilities - Udomiaye Emmanuel; Desy Osondu Eze; Kalu Cheche Kalu; Aminu Ahmad Haliru (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The emergence of the novel coronavirus, increase in microbial resistance and the scarceness of vaccines for the present pandemic have made it imperative to appraise the link between the sustainable built environment and Infection control as well as the strategies employed during the pre-antibiotic period. This paper aims to identify the nexus between a sustainable built environment and infection control in healthcare facilities with the view of developing guidelines and highlighting the role of architecture in curbing the pandemic. The study relied on existing studies, interviews, and interactions with healthcare workers. The findings showed that sustainable design strategies play a significant role in infection prevention and control and could as well be a panacea for curbing the spread of Coronavirus, especially in healthcare facilities. A sustainable environment for hospitals or healthcare facilities, apart from low energy and carbon emission, needs to integrate design strategies to confront the impact of healthcareassociated infections.